On the need for legal regulation of employee outsourcing - Więckiewicz-Szabłowska, Iwona (Problem zakresu regulacji ustawowej nietypowych form zarobkowania na przykładzie zatrudnienia zewnętrznego i pracy platformowej, 2025)
Employee outsourcing is a concept not defined by law, despite the fact that outsourcing contracts have been used in business practice for many years. In its proper form, it encompasses the situation where the service provider (outsourcer), as an entrepreneur, performs the obligations assumed under the outsourcing contract using its own employees, whom it actually manages in the work process. In market practice, however, the term outsourcing is also used to describe cases where the outsourcer’s service consists exclusively in the provision of employees who perform their duties under the permanent and direct management of the service recipient, which brings this construction closer to the model of temporary employment. The author analyses the possibility of a contractual transfer of the employer’s management to a third party, presenting the divergent jurisprudence of the Supreme Court in this respect. The author also assesses the need to regulate the legal construction of employee outsourcing in the aspect of both the model of proper and apparent outsourcing.